1996
DOI: 10.1038/nm0896-925
|View full text |Cite
|
Sign up to set email alerts
|

KSHV antibodies among Americans, Italians and Ugandans with and without Kaposi's sarcoma

Abstract: A major controversy regarding Kaposi's sarcoma-associated herpesvirus (KSHV or HHV8) is whether or not it is a ubiquitous infection of humans. Immunoassays based on KSHV- and Epstein-Barr virus (EBV)-coinfected cell lines show that most US AIDS-KS patients have specific antibodies to KSHV-related antigens. We have developed a sensitive indirect immunofluorescence assay (IFA) based on an EBV-negative, KSHV-infected cell line, BCP-1. When we used this IFA assay, KSHV-related antibodies were found in 71-88% of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
514
5
16

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 750 publications
(566 citation statements)
references
References 12 publications
30
514
5
16
Order By: Relevance
“…A body-cavity-related B-cell lymphoma cell, BCP-1, which is positive for KSHV and negative for Epstein -Barr virus, was used for an indirect immunofluorescence assay to detect IgG antibodies against KSHV antigen (Gao et al, 1996;Boshoff et al, 1998). Latently infected BCP-1 cells were fixed in 4% paraformaldehyde and were made permeable with 0.2% Triton X-100.…”
Section: Laboratory Diagnosesmentioning
confidence: 99%
See 2 more Smart Citations
“…A body-cavity-related B-cell lymphoma cell, BCP-1, which is positive for KSHV and negative for Epstein -Barr virus, was used for an indirect immunofluorescence assay to detect IgG antibodies against KSHV antigen (Gao et al, 1996;Boshoff et al, 1998). Latently infected BCP-1 cells were fixed in 4% paraformaldehyde and were made permeable with 0.2% Triton X-100.…”
Section: Laboratory Diagnosesmentioning
confidence: 99%
“…After the slides were washed in phosphate-buffered saline with 3% foetal calf serum, rabbit antihuman IgG labelled with fluorescein isothiocyanate (Dako, High Wycombe, UK), diluted 1 : 40 in phosphate-buffered saline with 3% foetal calf serum, was added and the slides were incubated at 228C for 20 min. The slides were then washed in phosphate-buffered saline without foetal calf serum and screened by ultraviolet microscopy for the nuclear stippling pattern characteristic of antibodies against the latent nuclear antigen of KSHV encoded by orf73 (Gao et al, 1996). In total, 416 samples were available for testing for antibodies against KSHV (32 cases and 384 controls).…”
Section: Laboratory Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-infected patients. have indicated that prexalence of HHV-8 correlates with KS occurrence (Gao et al 1996: Simpson et al 1996. This suggests that disease occurrence may reflect xirus prevalence.…”
Section: A) Prexvious Follow--upmentioning
confidence: 99%
“…(Chang et al, 1994;Gao et al, 1996). Such serological investigations were beyond the scope of the present study, which has instead explored other factors that may locally increase the risk of developing CKS in an area of relatively high incidence.…”
Section: Discussionmentioning
confidence: 98%